Myricetin inhibits transmissible gastroenteritis virus replication by targeting papain-like protease deubiquitinating enzyme activity - Fan, Jiahao; Xi, Pengyuan; Liu, Huimao; Song, Xu; Zhao, Xinghong; Zhou, Xun; Zou, Yuanfeng; Fu, Yuping; Li, Lixia; Jia, Renyong; Yin, Zhongqiong (Frontiers in Microbiology, 2024)
Myricetin, a natural flavonoid found in various foods, was investigated for its antiviral effect against transmissible gastroenteritis virus (TGEV). This α-coronavirus causes significant economic losses in the global swine industry. The study focused on the papain-like protease (PLpro), which plays a crucial role in coronavirus immune evasion by mediating deubiquitination. Targeting PLpro could potentially disrupt viral replication and enhance antiviral responses. The results demonstrated that myricetin effectively inhibited TGEV-induced cytopathic effects in a dose-dependent manner, with an EC50 value of 31.19 µM. Myricetin significantly reduced TGEV viral load within 48 h after an 8hour co-incubation period. Further investigations revealed that myricetin at a concentration of 100 μM directly inactivated TGEV and suppressed its intracellular replication stage. Moreover, pretreatment with 100 μM myricetin conferred a protective effect on PK-15 cells against TGEV infection. Myricetin competitively inhibited PLpro with an IC50 value of 6.563 µM. Molecular docking experiments show that myricetin binds to the Cys102 residue of PLpro through conventional hydrogen bonds, Pi-sulfur, and Pi-alkyl interactions. This binding was confirmed through sitedirected mutagenesis experiments, indicating myricetin as a potential candidate for preventing and treating TGEV infection.